The sustainability of reusing oil and gas produced water for agricultural irrigation in drylands - Echchelh, Alban (Cranfield University, 2019)
Produced water (PW) is the largest waste stream generated from oil and gas (O&G) extraction. Half of global PW (~8.5 km3 /year) is injected into deep disposal wells or discharged on the surface. These practices are controversial due to their environmental impacts causing increased regulation and cost. Meanwhile, water- scarce drylands host significant O&G resources. Reusing PW in irrigation provides an alternative to disposal options and could strengthen agriculture and food security in drylands. However, uncertainties exist regarding the sustainability of this practice. This research addresses these knowledge gaps by evaluating the agro-environmental sustainability and the financial cost of reusing PW in irrigation. First, the existing knowledge about PW irrigation is reviewed to identify the agro-environmental risks posed by this practice and the uncertainties regarding its sustainability. Second, irrigation with PW is simulated using a soil- water model to identify the parameters related to the environment and to the irrigation management which determine the sustainability of irrigation. Finally, a framework combining irrigation modelling and a cost analysis is applied in both regional and industrial case studies to identify agro-environmentally sustainable irrigation strategies with PW and estimate their operating costs. This research demonstrates that irrigation with PW can be agro-environmentally sustainable if natural conditions are favourable such as on gypsum-rich draining soils in the least arid climates. Furthermore, adapted management combining irrigation at a little over the crop water needs (100–110% of the crop water needs) and PW blending in a 1:1 up to 1:4 ratio with treated sewage effluent or desalinated PW can achieve agro-environmentally sustainable irrigation by preserving soil fertility, crop yield and groundwater quality. The cost of managing PW in irrigation estimated between $0.19–$1.09/m³ , is higher or within the cost range of surface PW discharge and lower or within the cost range of injecting PW into deep disposal wells. Further research is needed to test and validate the modelling results in field conditions. A case-by-case approach is recommended to assess the broader economic and social impacts of reusing PW in irrigation.
Keywords: Arid climate; modelling; salinity; sodicity; wastewater reuse; agro-environmental risks